2016
DOI: 10.1186/s12894-016-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Global expression of AMACR transcripts predicts risk for prostate cancer – a systematic comparison of AMACR protein and mRNA expression in cancerous and noncancerous prostate

Abstract: Background: The high false negative rates for initial prostate biopsies refer a large number of the men for repeat biopsies each year. Therefore, biomarkers associated with high risk of the presence of malignancy in histologically benign biopsies could provide a tool to discriminate the patients who need repeat biopsy or intensive follow-up from those who do not. Here we examined the diagnostic applicability of alpha-methylacyl CoA racemase (AMACR) and androgen receptor (AR) mRNA expression and AMACR protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Recently, PC specific ERG rearrangements and altered epigenetic regulations of AMACR at the protein level were evaluated to allocate high PC risk in diagnostically challenging prostate cores including ASAP. [15][16][17][33][34][35][36][37][38][39][40] Although ERG and AMACR have stood out as PC indicators at the protein level in the literature, currently existing results are conflicting and should be validated as this is most likely due to methodological approaches (fluorescence in situ hybridization, immunohistochemistry [IHC] or qPCR), ethnic origin of the patients that is an important factor affecting the fusion frequency in the population of interest, and the differences in clinicopathological characteristics of patients. In the present study, we analyzed all PC-related markers using a RT-qPCR system which offers a more sensitive detection option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PC specific ERG rearrangements and altered epigenetic regulations of AMACR at the protein level were evaluated to allocate high PC risk in diagnostically challenging prostate cores including ASAP. [15][16][17][33][34][35][36][37][38][39][40] Although ERG and AMACR have stood out as PC indicators at the protein level in the literature, currently existing results are conflicting and should be validated as this is most likely due to methodological approaches (fluorescence in situ hybridization, immunohistochemistry [IHC] or qPCR), ethnic origin of the patients that is an important factor affecting the fusion frequency in the population of interest, and the differences in clinicopathological characteristics of patients. In the present study, we analyzed all PC-related markers using a RT-qPCR system which offers a more sensitive detection option.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, diagnostic utility of AMACR has been suggested in diagnostically challenging prostatic tissue samples due to altered expression in PC, and due to high specificity and sensitivity at both the transcriptional and translational level. 28,36,[38][39][40][41][42][43][44][45][46] AMACR expression at the RNA level, but not at the protein level, was also reported to be a predictive marker for PC risk in tissue samples of the patients with negative biopsies. 47 We emphasized in detail that the expression of AMACR should be assessed at the mRNA level, due to RNA/protein discordancy, when evaluating PC risk in biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA transcript expression of ACSM1, AMACR, CACNA1D, DLX1, PCA3, PLA2G7, RHOU, SPINK1, SPON2, TMPRSS2‐ERG, and TDRD1 genes were evaluated in the biopsy cores taken from the peripheral zone of the prostate without IMPROD bpMRI evidence of suspicious lesion. Total RNA was extracted from the tissues using RNeasy Mini kit (Qiagen, Chatsworth, CA) with the modification of adding a known, fixed amount of artificial internal control RNA to each sample after cell lysis as described previously . Total RNA was reverse transcribed into cDNA using the High Capacity cDNA Archive kit (Applied Biosystems, Foster City, CA) using the random primers provided in the kit.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, expressions of 11 genes (ie, ACSM1, AMACR, CACNA1D, DLX1, PCA3, PLA2G7, RHOU, SPINK1, SPON2, TMPRSS2‐ERG, and TDRD1) in histologically benign prostate tissue from PCa patients were investigated to determine their diagnostic performance . Furthermore, it has been shown that the expression of TDRD1 and TMPRSS2‐ERG mRNA is significantly different ( P < 0.05) in men with PCa compared with men without PCa .…”
mentioning
confidence: 99%
“…The AMACR gene codes for an enzyme involved in peroxisomal beta oxidation of branched fatty acids [70,71] and is highly overexpressed in prostate cancer [72,73], the most prevalent cancer in the male population, and is used as a well-established diagnostic marker. However, the exact mechanisms causing dysregulation of AMACR expression remain elusive [74,75].…”
Section: Introductionmentioning
confidence: 99%